A unifying theme for stray cats? Issues in heterodox discourses - Paolo Ramazzotti (PSL Quarterly Review)
The article discusses three books (Whalen, 2022a; Westra 2022; Chester and Jo, 2022a) that deal with the need for a heterodox approach to economics from a variety of perspectives. It discusses the possibility of achieving a unifying theme that characterizes heterodox economics along with the existence of a commonly accepted criterion to assess the quality of economic research. It points to the importance of a variety of lively research perspectives that pursue well-being rather than the quest for an all-encompassing, unitary theory of the economy. A major goal, to this end, is greater dialogue among the different strands of thought.